Reliability and validity of the Spanish version of the Children's Sleep Habits Questionnaire (CSHQ-SP) in school-age children. - Lucas‐de la Cruz, L.; Martínez‐Vizcaino, V.; Álvarez‐Bueno, C.; Arias‐Palencia, N.; Sánchez‐López, M.; Notario‐Pacheco, B. (Child: Care, Health & Development, 2016)
Background Sleep disorders in schoolchildren are a common problem worldwide, and when are not adequately diagnosed and treated, their negative impact on daytime functioning may be significant. The aim of this study was to evaluate the psychometric properties of the Spanish version of the Children's Sleep Habits Questionnaire (CSHQ). Methods Participants were 286 school-aged children from a community-based sample, aged 4 to 7 years. The sleep behaviour was evaluated using the CSHQ and actigraphy (ActiSleep monitor). The CSHQ was adapted to the Spanish language. The internal consistency of the questionnaire and the test-retest reliability between scores at baseline and three-weeks-later were estimated. Associations between CSHQ items and accelerometer sleep quality indicators were used as indicators of concurrent validity. Results Cronbach's alpha coefficients for the subscales ranged from 0.60 to 0.81, and 0.81 for the full scale; the intraclass correlation coefficients ranged from 0.56 to 0.81. A moderate correlation was observed in sleep latency and awakenings measurements using both parents' reported sleep habits (CSHQ-SP) and sleep quality indicators (ActiSleep). Conclusions The CSHQ-SP has demonstrated adequate psychometric properties, and it serves as a useful instrument for clinical and research setting.